Clinical features and short-term outcomes of COVID-19 in Tehran, Iran: An analysis of mortality and hospital stay - Kashefizadeh, Alireza; Ohadi, Laya; Golmohammadi, Maryam; Araghi, Farnaz; Dadkhahfar, Sahar; kiani, Arda; Abedini, Atefeh; Fadaii, Abbas; Ghojoghi, Alieh; Nouraie, Mehdi; Tabary, Mohammadreza (Acta Biomedica Atenei Parmensis, 2020)
BackgroundThe sudden outbreak of the COVID-19 disease originated in Wuhan, China, in December 2019. There have been few reports of the clinical course of the disease, but detailed information on the risk factors for increased hospital stay and mortality is not available. In this study, we aimed to present the details of 53 confirmed COVID-19 cases to share the clinical course and the risk factors for longer hospital stay and death.MethodsIn this study, we enrolled fifty-three patients with confirmed COVID-19 infection from a referral academic hospital in Tehran, Iran admitted between March and April 2020. Patients’ demographics, laboratory tests, treatments, length of hospital stay (LOHS), and final outcome were recorded and analyzed.ResultsFifty-three patients were included in this study. The higher LOHS was associated with clinical symptoms, including hemoptysis (IRR= 0.73, P-value= 0.02), diarrhea (IRR= 0.78, P-value= 0.01), headache (IRR= 0.81, P-value= 0.05), and dry cough (IRR= 0.82, P-value= 0.05). Mortality was associated with older age(Odds ratio=1.148, 95%CI=1.032-1.276), lower calcium level (Odds ratio=0.087, 95%CI=0.010-0.788), lower serum albumin (Odds ratio=0.036, 95%CI=0.002-0.655), as well as increased level of neutrophil/lymphocyte ratio (NLR) (Odds ratio=1.468, 95%CI=1.086-1.985), lactate dehydrogenase (LDH) (Odds ratio=1.004, 95%CI=1.000-1.007), and urea (Odds ratio=1.023, 95%CI=1.006-1.039). Conclusion Our study identified that decreased levels of O2saturation, platelet count, calcium, albumin, and increased NLR, LDH, urea, and old age were correlated with mortality. Also, LOHS was significantly associated with clinical findings, such as hemoptysis and diarrhea.